Assessment of Cardiac Autonomic Function by Short-Term Sensor-Based and Long-Term Heart Rate Variability Analyses in Individuals with Spinal Cord Injury After Long-Term Table Tennis Training - Georgia Vogiatzi; Vasiliki Michou; Nikos Malliaropoulos; Vasileios Tsimaras; Asterios Deligiannis; Evangelia Kouidi (Sensors, 2024)
This study aimed to examine the acute and chronic effects of an exercising table tennis program on cardiac Autonomic Nervous System (ANS) and functional capacity in people with tetraplegia. Twenty males with tetraplegia (C6–C7), with a mean age of 38.50 ± 4.04 years old, were randomly assigned into two equal groups: A, who followed a 6-month exercise training program with table tennis 3 times per week, and B, who remained untrained. Additionally, 11 healthy sedentary men (group C) with a mean age of 39.71 ± 5.87 years old participated in the study as healthy controls. At baseline, all participants underwent a short-term (5 min) and a long-term (24 h ambulatory) ECG monitoring to evaluate the heart rate variability (HRV) indices and a maximal arm ergometric and dynamometric testing of the upper limbs. Moreover, the acute cardiac autonomic responses to maximal arm cycle exercise test were evaluated by Polar S810i sensor chest strap. At the end of the 6-month study, all parameters were revaluated only in groups A and B. At baseline, there was no statistically significant difference between the two patient groups. However, intra-group changes at the end of the 6-month study regarding the 24-h HRV monitoring indicated that group A statistically increased the standard deviation of R-R intervals (SDNN) by 13.9% (p = 0.007), the standard deviation of R-R intervals calculated every 5 min (SDANN) by 8.4% (p = 0.007), the very low frequency (VLF) by 7.1% (p = 0.042), and the low frequency [LF (ms2)] by 10.5% (p = 0.009), which almost reached the levels of group C. Favorable improvements were also noticed at the end of the study for group A in maximal exercise time of the upper limbs by 80.4% (p < 0.001) and maximal strength of the right hand by 27.8% (p < 0.001). Linear regression analysis after training showed that maximal exercise time was positively correlated with SDNN (r = 0.663, p = 0.036) and with LF (ms2) (r = 0.623, p = 0.045). Our results indicate that a 6-month table tennis training program is efficient and can improve cardiac ANS activity mainly by increasing sympathovagal balance.